Performance of an axial flow helium compressor under high through-flow conditions - De Wet, Christiaan Louis (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.